Report of the Working Group on Civil Violence and Civil War at the Civil Resistance International Workshop - Marsili, M.; Meisch, S.; Jugo, J.; Naeem, H.; Ostendorf, T.; Saleviev, D. (2021)
Report presented by Working Group D – When might civil violence, even civil war, be justified? at the International Graduate Workshop "Civil Resistance – How Peoples, Ideas and Movements can change Politics", held online on 5–7 October 2021, organized by Oxford University, Göttingen University, Stiftung Adam von Trott, Imshausen e.V.